Ultrasonographic imaging of normal reticulum and traumatic reticuloperitonitis in crossbred cows - Sheikh Imran; Shivali Sharma; Abid Ali Bhat (Eurasian Journal of Veterinary Sciences)
Aim: To describe observations based on ultrasonographic examination of the reticulum in healthy crossbred cows and to compare with cows suffering from traumatic reticuloperitonitis. Materials and Methods: Ultrasonographic examinations were performed on 10 non-pregnant cows. The reticulum was scanned at the level of elbow in the left 7th to 5th intercostal spaces (ICSs) and the right 7th to 6th ICSs as well as in the median, the right paramedian, and the left paramedian regions. Crossbred adult cows suffering from traumatic reticuloperitonitis were also evaluated ultrasonographically for comparison with the clinically healthy cows. Results: The reticular wall was seen as a thick echogenic line adjacent and caudal to diaphragm. The amplitude of the first reticular contraction ranged from 5.6 to 10.4 cm. Echogenic bands between the reticulum and the diaphragm, and deposits of heterogeneous echostructures (consisting of echogenic fibrin and hypoechogenic fluid) on the surfaces of reticulum, rumen, spleen, liver, and omasum were observed, representing local peritonitis. Conclusions: More routine use of ultrasonography may aid in early diagnosis of traumatic reticuloperitonitis and detection of its sequelae, which are difficult to detect by clinical examination alone.